A Survey on Ontology-Based Systems to Support the Prospection, Diagnosis and Treatment of Breast Cancer - Isac, Cassia; Viterbo, José; Conci, Aura (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2016: Anais do XII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2016.5972, 2016)
In a scenario where there is a huge amount of available data sources, the Semantic Web has played a key role in sharing, retrieval, selection, and combination of data organized in various formats. The storage and retrieval of medical images manipulated by systems that support breast cancer detection can take great advantage from the use of such technology. In this paper we present a comprehensive study on ontology-based systems that support the manipulation of medical images related to breast cancer, identifying the main features of each approach.